Haloperoxidase Mimicry by CeO2−x Nanorods Combats Biofouling. Issue 4 (29th November 2016) - Herget, Karoline; Hubach, Patrick; Pusch, Stefan; Deglmann, Peter; Götz, Hermann; Gorelik, Tatiana E.; Gural'skiy, Il'ya A.; Pfitzner, Felix; Link, Thorben; Schenk, Stephan; Panthöfer, Martin; Ksenofontov, Vadim; et al.
Abstract : CeO2− x nanorods are functional mimics of natural haloperoxidases. They catalyze the oxidative bromination of phenol red to bromophenol blue and of natural signaling molecules involved in bacterial quorum sensing. Laboratory and field tests with paint formulations containing 2 wt% of CeO2− x nanorods show a reduction in biofouling comparable to Cu2 O, the most typical biocidal pigment.